Virtual Reality Therapy for the Management of Chronic Spinal Pain: Systematic Review and Meta-Analysis - Tongtong Zhang; Xin Li; Xuan Zhou; Lixia Zhan; Fan Wu; Zefan Huang; Yuxun Sun; Yufei Feng; Qing Du (JMIR Publications, 2024)
BackgroundThe effectiveness of virtual reality (VR) therapy in adults with chronic spinal pain (CSP) is unclear. ObjectiveThis study was conducted to compare the effectiveness of VR therapy and other therapies in adults with CSP, especially patients with inflammation-related pain. MethodsPubMed, Web of Science, Cochrane Library, Embase, and CINAHL databases were searched up to November 11, 2023. Randomized controlled trials (RCTs) comparing adults with CSP receiving VR therapy with those receiving other therapies were included. The trial registration platform as well as the reference lists of included studies and previous systematic reviews and meta-analyses were manually searched. Two independent reviewers performed study selection, data extraction, risk-of-bias assessment, and evaluation of the quality of the evidence. The weighted mean difference (WMD) was used as the effect size used to synthesize the outcome measure. ResultsIn total, 16 RCTs involving 800 participants were included in this meta-analysis. The pooled data from 15 (94%) RCTs including 776 (97%) participants showed that VR therapy was superior in improving pain intensity (WMD=-1.63, 95% CI -2.11 to -1.16, P<.001, I2=90%) and reducing inflammatory markers, including C-reactive protein (WMD=-0.89, 95% CI -1.07 to -0.70, P<.001, I2=0%), tumor necrosis factor-alpha (WMD=-6.60, 95% CI -8.56 to -4.64, P<.001, I2=98%), and interleukin-6 (WMD=-2.76, 95% CI -2.98 to -2.53, P<.001, I2=0%). However, no significant differences were found in terms of the spinal range of motion (ROM), disability level, or fear of movement. In addition, 10 (63%) of the included RCTs had a high risk of bias. ConclusionsVR therapy may be an effective and safe intervention for reducing symptoms in patients with CSP, as it is shown to exert significant analgesic effects and beneficial improvements in inflammatory factor levels. However, this approach may not have significant effects on the spinal ROM, disability level, or fear of movement. Notably, the quality of the evidence from the RCTs included in this study ranged from moderate to low. Therefore, we recommend that readers interpret the results of this study with caution. Trial RegistrationPROSPERO CRD42022382331; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=382331